A Concise Synthesis of 6H-Indolo[2,3-b]quinolines: Formal Synthesis of Neocryptolepine - Kadam, Hari K.; Parvatkar, Prakash T.; Tilve, Santosh G. (Synthesis, 2012)
A new two-step approach for the synthesis of 6H-indolo[2,3-b]quinolines is described using indole C3 alkylation and a one-pot reduction–cyclization–aromatization sequence. The synthesis of the parent 6H-indolo[2,3-b]quinoline system constitutes a formal synthesis of the alkaloid neocryptolepine (cryptotackieine).
Keywords: alkaloid; alkylation; indoloquinoline; reduction–cyclization; domino reaction